Pelatihan Pengukuran Antropometri Balita pada Kader Posyandu di Desa Wonorejo - Rahmatika, Qory Tifani; Widjayanti, Yhenti; Masfi, Achmad (Universitas Baiturrahim, 2024)
Millions of Indonesian children remain at risk due to the high burden of double malnutrition. Close monitoring of the growth and development status of toddlers is of utmost importance, particularly the role of community health workers in early detection if any growth disorders are observed in toddlers. The purpose of this community engagement is to enhance the understanding of community health workers at integrated health posts (posyandu) in conducting anthropometric measurements and instructing them in evaluating nutritional status based on anthropometric measurements. The methods employed in this training activity include lectures, demonstrations, re-demonstrations, as well as post-training discussions. The results of knowledge and skills assessments among the community health workers, including weighing, measuring height or length, and head circumference measurements, after the training, indicate that the majority of community health workers can accurately perform anthropometric measurements. Training using methods of lecture, discussion, and demonstration-redemonstration is considered effective in enhancing the knowledge and skills of cadres in anthropometric measurements.